If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -2) + -7(4 + -1x) = 0 Reorder the terms: 7(-2 + x) + -7(4 + -1x) = 0 (-2 * 7 + x * 7) + -7(4 + -1x) = 0 (-14 + 7x) + -7(4 + -1x) = 0 -14 + 7x + (4 * -7 + -1x * -7) = 0 -14 + 7x + (-28 + 7x) = 0 Reorder the terms: -14 + -28 + 7x + 7x = 0 Combine like terms: -14 + -28 = -42 -42 + 7x + 7x = 0 Combine like terms: 7x + 7x = 14x -42 + 14x = 0 Solving -42 + 14x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 42 + 14x = 0 + 42 Combine like terms: -42 + 42 = 0 0 + 14x = 0 + 42 14x = 0 + 42 Combine like terms: 0 + 42 = 42 14x = 42 Divide each side by '14'. x = 3 Simplifying x = 3
| x(6x-11)=21 | | 28x+140=-28 | | 3(k+6)=-(k-3) | | x^2+1-2x/x^2-1 | | 2/3x-11=y+4 | | 5/8b+5=10 | | y=3/4x-6 | | 2u2/21 | | 2*22/7*1/3 | | 5/9y=32 | | (9x+8)(9x+8)=81x^2+64 | | 3(5-x)=-3x+12 | | 15x+108=33 | | f(x)=10+5x | | n(283.2)=158.13 | | -2a-3=3a+7 | | 7p+7=6(p+5) | | 15x+183=33 | | -4(m-8)=3m-3 | | 2(x+3)(x-5)=0 | | 3x+y=42 | | 1/6-11/12x+1=6 | | x^3+6x^2+3x=-18 | | 5x+3x+4x=189 | | 3-4/5w=-9 | | 2y+43=2 | | x^3-3x^2-x=-3 | | 2(-2)+4y=-16 | | (x+8)2=(x+7)2 | | -6-5=-8+x | | -7c+1=-27 | | 9x^4-42x^3+49x^2=0 |